How to Reveal the Meaning of Space in Vernacular Architecture? (International Journal of Built Environment and Sustainability, 2021)
Vernacular architecture is a modest style of building used to maintain the balance of human relations with nature. This architectural style is specific to a region and passed down from one generation to another to embody cultural values. However, its development is currently facing globalization and modernization challenges, thereby leading to a gradual shift of this ancestral heritage to modern buildings. Change is unavoidable due to continuous evolution, however, the meaning inherent architecture buildings need to be maintained because it contains the cultural and social values of the associated local community. Furthermore, vernacular building space is a place for social activities and contains historical meaning applicable to modern buildings. Its functionality responds to changes and the needs of times while maintaining the local essence. Therefore, this research aims to determine the suitable method needed to reveal the meaning of vernacular architectural space. Data were collected from the conscious mind of space users through in-depth interviews by applying epoche, which were further reduced, categorized, and integrated to determine its meaning. The data collected through a literature review were analyzed using the content analysis method. The results showed that transcendental phenomenology is the right method to determine the meaning of vernacular architectural space. Based on the results, it is concluded that the meaning passed down from one generation to another could be expressed through the conscious experience of space users. Furthermore, transcendental phenomenology helped reveal the meaning without the intervention of the author’s knowledge, therefore it is unbiased and applicable in modern buildings.